2017
DOI: 10.1002/2016ja023471
|View full text |Cite
|
Sign up to set email alerts
|

IMF dependence of energetic oxygen and hydrogen ion distributions in the near‐Earth magnetosphere

Abstract: Energetic ion distributions in the near‐Earth plasma sheet can provide important information for understanding the entry of ions into the magnetosphere and their transportation, acceleration, and losses in the near‐Earth region. In this study, 11 years of energetic proton and oxygen observations (> ~274 keV) from Cluster/Research with Adaptive Particle Imaging Detectors were used to statistically study the energetic ion distributions in the near‐Earth region. The dawn‐dusk asymmetries of the distributions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
(61 reference statements)
2
24
0
Order By: Relevance
“…There is a 1 order of magnitude difference between the SH and NH, which could be explained by the different relative location of the spatial boxes and the geomagnetic activity. A similar trend has been observed by Luo et al (2017), who studied the energetic ion distributions in the dayside magnetosphere and the plasma sheet. The authors found that there is a strong correlation between the dawn-dusk asymmetry and the IMF direction, with a higher asymmetry in the Southern Hemisphere.…”
Section: Most Extreme Casesupporting
confidence: 84%
“…There is a 1 order of magnitude difference between the SH and NH, which could be explained by the different relative location of the spatial boxes and the geomagnetic activity. A similar trend has been observed by Luo et al (2017), who studied the energetic ion distributions in the dayside magnetosphere and the plasma sheet. The authors found that there is a strong correlation between the dawn-dusk asymmetry and the IMF direction, with a higher asymmetry in the Southern Hemisphere.…”
Section: Most Extreme Casesupporting
confidence: 84%
“…It is observationally known that~10-100 keV ions are the main components of the storm time ring current (e.g., Daglis et al, 1999;Kronberg et al, 2017) and that they are supplied into the ring current by convective transport (e.g., Gkioulidou et al, 2016). Luo et al (2017) reported that energetic (≳274 keV) oxygen ions can be transported to the dayside outer magnetosphere and plasma sheet via reconnection at the magnetopause. Lanzerotti and Gerrard (2016) and Gkioulidou et al (2016) reported that >100 keV protons are transported into the ring current by diffusive transport.…”
Section: Introductionmentioning
confidence: 99%
“…Lanzerotti and Gerrard (2016) and Gkioulidou et al (2016) reported that >100 keV protons are transported into the ring current by diffusive transport. Luo et al (2017) reported that energetic (≳274 keV) oxygen ions can be transported to the dayside outer magnetosphere and plasma sheet via reconnection at the magnetopause. However, there are few reports on radial transport of ≳100 keV oxygen ions into the ring current.…”
Section: Introductionmentioning
confidence: 99%
“…They found O + was the dominant contributor to the mass density (30 %) in the duskside magnetopause in comparison to 3 % in the dawnside and 4 % near noon. The dawn-dusk asymmetries of the energetic O + (>∼ 274 keV) distribution in three different regions (dayside magnetopause, near-Earth nightside plasma sheet, and tail plasma sheet) are also observed by Luo et al (2017). They found that the energetic O + distributions were mainly influenced by the dawn-dusk IMF directions and the enhancement of ion intensity strongly related to the location of the magnetopause reconnection.…”
Section: Introductionmentioning
confidence: 97%
“…The distribution of energetic oxygen ion density at the dayside magnetopause is asymmetric, and it has a close relationship with the interplanetary magnetic field (IMF) (e.g., Bouhram et al, 2005;Phan et al, 2004;Luo et al, 2017). Bouhram et al (2005) pointed out that the O + density in the duskside (on average 0.053 cm −3 ) magnetopause is higher than that in the dawnside (on average 0.014 cm −3 ).…”
Section: Introductionmentioning
confidence: 99%